2013
DOI: 10.1002/cm.21122
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cytoskeletal protein function in cells by means of nanobodies

Abstract: Nanobodies or VHHs are single domain antigen binding fragments derived from heavy-chain antibodies naturally occurring in species of the Camelidae. Due to their ease of cloning, high solubility and intrinsic stability, they can be produced at low cost. Their small size, combined with high affinity and antigen specificity, enables recognition of a broad range of structural (undruggable) proteins and enzymes alike. Focusing on two actin binding proteins, gelsolin and CapG, we summarize a general protocol for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Depending on their binding properties they can be used to visualize subcellular antigen location or to modulate their target structure and function (31,33,43,55,71). Here, we have demonstrated that all selected nanobodies are able to bind ␤-catenin in living cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Depending on their binding properties they can be used to visualize subcellular antigen location or to modulate their target structure and function (31,33,43,55,71). Here, we have demonstrated that all selected nanobodies are able to bind ␤-catenin in living cells.…”
Section: Discussionmentioning
confidence: 82%
“…Intracellular Application of ␤-catenin Chromobodies-Recently, we and others have shown that V H H domains derived from heavy chain antibodies of camelids can be selected as intrabodies for functional interference and visualization of target structures (31,33,54,55). To detect endogenous ␤-catenin within living cells, we fused the coding sequences of the nanobodies to the fluorescent protein tagGFP generating so-called chromobodies (BC-chromobodies) and introduced them on DNA-level either by transfection or viral transduction in living cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nanobodies are emerging as versatile tools in biotechnology. Several recent studies incorporated ITC to characterize nanobodies function and structure [55][56][57].…”
Section: Beyond Monoclonal Antibodiesmentioning
confidence: 99%
“…Moreover, in this way, one can also disturb protein function by restricting free diffusion of the protein and limiting its availability at places where it is needed [71]. Considering that the paratope of the nanobody is located at its N-terminal end, it is safer to fuse the tag at the C-terminal end of the nanobody.…”
Section: Antibody Engineering 216mentioning
confidence: 99%